Understanding variation in person-centered maternity care: Results from a household survey of postpartum women in 6 regions of EthiopiaAJOG Global Reports at a Glance - Elizabeth K. Stierman, PhD; Linnea A. Zimmerman, PhD; Solomon Shiferaw, PhD; Assefa Seme, MD; Saifuddin Ahmed, PhD; Andreea A. Creanga, MD (Elsevier, 2023)
BACKGROUND: Effective communication, respect and dignity, and emotional support are critical for a positive childbirth experience that is responsive to the needs and preferences of women. OBJECTIVE: This study evaluated the performance of a person-centered maternity care scale in a large, representative household sample of postpartum women, and it describes differences in person-centered maternity care across individuals and communities in Ethiopia. STUDY DESIGN: The study used data from 2019 and 2020 from a representative sample of postpartum women in 6 regions of Ethiopia. It measured person-centered maternity care using a scale previously validated in other settings. To assess the scale validity in Ethiopia, we conducted cognitive interviews, measured internal consistency, and evaluated construct validity. Then, we fit univariable and multivariable linear regression models to test for differences in mean person-centered maternity care scores by individual and community characteristics. Lastly, multilevel modeling separated variance in person-centered maternity care scores within and between communities. RESULTS: Effective communication and support of women's autonomy scored lowest among person-centered maternity care domains. Of 1575 respondents, 704 (44.7%) were never asked their permission before examinations and most said that providers rarely (n=369; 23.4%) or never (n=633; 40.2%) explained why procedures were done. Person-centered maternity care was significantly higher for women with greater wealth, more formal education, and those aged >20 years. Variation in person-centered maternity care scores between individuals within the same community (τ2=58.3) was nearly 3 times greater than variation between communities (σ2=21.2). CONCLUSION: Ethiopian women reported widely varying maternity care experiences, with individuals residing within the same community reporting large differences in how they were treated by providers. Poor patient-provider communication and inadequate support of women's autonomy contributed most to poor person-centered maternity care.